Role of long noncoding RNA KCNQ1 overlapping transcript 1/microRNA-124-3p/BCL-2-like 11 axis in hydrogen peroxide (H2O2)-stimulated human lens epithelial cells. Issue 3 (1st March 2022) - Xu, Yue; Zheng, Yanhua; Shen, Pincheng; Zhou, Liping
ABSTRACT: Age-related cataract (ARC) is one of the most common causes of vision loss in aging people. This research analyzed the functions and mechanism of long noncoding RNA KCNQ1 overlapping transcript 1 (KCNQ1OT1) in hydrogen peroxide (H2 O2 )-stimulated human lens epithelial cells (SRA01/04 cells) in ARC. SRA01/04 cells were stimulated with 200 µM H2 O2 to establish oxidative damage in the ARC model. A MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay and flow cytometry analysis were conducted to evaluate cell growth and apoptosis. The relevance between KCNQ1OT1 and microRNA (miR)-124-3p or miR-124-3p and BCL-2-like 11 (BCL2L11) was measured through Starbase and a dual luciferase reporter gene assay. The levels of KCNQ1OT1 and miR-124-3p were assessed via quantitative real-time polymerase chain reaction (qRT-PCR). We observed that KCNQ1OT1 was over-expressed and miR-124-3p was low-expressed in H2 O2 -stimulated SRA01/04 cells. KCNQ1OT1 interacted with miR-124-3p and negatively mediated its levels. In addition, KCNQ1OT1-siRNA reversed the effects of H2 O2 on SRA01/04 cells, evidenced by enhanced cell viability, inhibited apoptotic cells, promoted Bcl-2 expression, and reduced Bax levels. Nevertheless, these observations were inverted after miR-124-3p inhibitor treatment. Likewise, miR-124-3p mimic had a protective effect on H2 O2 -stimulated SRA01/04 cells. Our data suggested that BCL2L11 targeted miR-124-3p directly. In summary, the data indicated that lncRNA KCNQ1OT1 down-regulation protected SRA01/04 cells from oxidative stress stimulated damage via the miR-124-3p/BCL2L11 pathway. GRAPHICAL ABSTRACT: uf0001